2022
DOI: 10.1038/s41467-022-32029-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong organic phosphorescence from isolated molecules with repulsive interactions for multifunctional applications

Abstract: Intermolecular interactions, including attractive and repulsive interactions, play a vital role in manipulating functionalization of the materials from micro to macro dimensions. Despite great success in generation of ultralong organic phosphorescence (UOP) by suppressing non-radiative transitions through attractive interactions recently, there is still no consideration of repulsive interactions on UOP. Herein, we proposed a feasible approach by introducing carboxyl groups into organic phosphors, enabling form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…One can see that BI crystals are packed more closely than NMeBI. This point can also be supported by comparing their crystal densities (BI: 1.471 g/cm 3 > NMeBI: 1.347 g/cm 3 ). Therefore, it can be concluded that the rigid environment created by abundant hydrogen bonds and π−π stacking is responsible for the observed pRTP in the doped crystals.…”
mentioning
confidence: 71%
“…One can see that BI crystals are packed more closely than NMeBI. This point can also be supported by comparing their crystal densities (BI: 1.471 g/cm 3 > NMeBI: 1.347 g/cm 3 ). Therefore, it can be concluded that the rigid environment created by abundant hydrogen bonds and π−π stacking is responsible for the observed pRTP in the doped crystals.…”
mentioning
confidence: 71%
“…Additionally, according to El-Sayed’s rule, the magnitude of SOC (and therefore the ISC) can be elevated by promoting the non-bonding characteristic (n) to π–π* transitions. In such a context, different non-covalent interactions such as halogen bonding, intermolecular electronic coupling of π and n moieties, and efficient π–π stacking by H-aggregation have been proposed to promote ISC, leading to efficient RT phosphorescence. To understand the ISC routes, TD-DFT calculations have been performed in the monomeric and aggregated (dimer, trimer, tetramer, and large cluster) state at the TPPSh-D3BJ/Def2TzVP level of theory. The calculated excited electronic state energy levels are tabulated in Table S1a–f and diagrammatically summarized in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular H-bonding and halogen bonding are the major interactions to inhibit the nonradiative transitions and oxygen quenching of triplet excitons . High-performance host–guest doped materials are expected to be constructed through the emergence of molecular interactions such as ionic bonding, coordination bonding, and hydrophobic interactions. ,, Moreover, novel doped RTP systems with chirality, specific recognizability, or biological targeting can be constructed through the introduction of corresponding functional groups, which will promote the future development of intelligent response RTP materials.…”
Section: Internal Stimulus Rtp Materials With a Third Componentmentioning
confidence: 99%